Histological Structure of Stingrays (Gymnura poecilura) Heart - Yani, Desi Arsita (Proceeding International Conference on Science and Engineering, 2017)
Stingrays belong to the sub class of Elesmobranchii or often termed as cartilaginous fish. The heart is one of the circulating organs in fish that serves to pump blood throughout the body. The fish circulatory system is a closed system with a single blood circulation. This study aims to determine the histological structure of stingrays' hearts. The fish used for this study are butterfly stingray (Gymnura poecilura) obtained from Depok Beach, Bantul. The equipments used in this research are a set of surgical instrument, bottles, paraffin board, razor blades, embedding cassettes, staining jar, microtomes, slide glass, cover glass, and binocular microscopes. Materials used are stingrays, chloroform, bouin, alcohol, xylol, aquades, paraffins, hematoxylin and eosin, albumin, and entelan. The staining used in this research is HE (Hematoxylin-Eosin) method. Based on the results of the research and observation, the heart of stingrays consists of epicardium, endocardium, myocardium, muscle cells, and cell nuclei. Epicardium is the outermost layer of the heart that is coated by the tissue as a protective. The inner endocardium is coated with epithelial cells. Myocardium are the middle layer of heart wall. The smooth muscle cells are the heart muscle. Cell nuclei are usually present in smooth muscle cells.